РЕЗУЛЬТАТИ АПРОБАЦІЇ ІМУНОФЕРМЕНТНОЇ ТЕСТСИСТЕМИ ДЛЯ ВИЯВЛЕННЯ ІМУНОГЛОБУЛІНІВ КЛАСУ G ДО ВІРУСУ ХВОРОБИ ТЕШЕНА В СИРОВАТКАХ КРОВІ СВИНЕЙ - Бова , Т.О.; Сорока , В.І. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2006)
The results of approbation of immuno-enzyme test-system for detection antibody against Teschen disease virus in porcine serums are presented. It’s shown that this worked out test-system has permitted to determine the immune status of animal and the efficiency of application vaccines in farms.